Radioactive waste management and the law / Az Azimah Abd Aziz and Siti Aminah Ali - Abd Aziz, Az Azimah; Ali, Siti Aminah (2008)
This project paper studies the law on radioactive waste management in Malaysia. Since there is no specific law on radioactive waste management, the focus of this research is on Atomic Energy Licensing Act 1984 (Act 304) because it contained provision on Atomic Energy including radioactive material and radioactive waste. The aim of this research is to examine the Act and to see whether the Act is sufficient enough to protect the public health and the environment. The application of the law on radioactive waste management and its strength and weaknesses will be looked at. Act 304 is the Parent Act that delegates its power to the Atomic Energy Licensing Board (AELB). The AELB has power to make the regulations regarding to radioactive control but at the moment in Malaysia, there is no specific regulation on radioactive and its waste management. The Malaysian law currently is too wide and it is not as strict as other countries such as Japan. This study use the qualitative method approach where information was gathered from interviews, reviews of literature sources including online articles and journals and issues concerning the radioactive waste management. Thus, the research recommends that the law needs to be more specific and strict in order to protect the public and the environment.